HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP KELUARGA DENGAN PERILAKU DALAM MENINGKATKAN KAPASITAS FUNGSIONAL PASIEN PASCA STROKE DI WILAYAH KERJA PUSKESMAS KARTASURA - Irdawati, Irdawati; Ambarwati, Winarsih Nur (Jurnal Berita Ilmu Keperawatan, 2009)
Stroke patient is not total healing, hence if we handle with good so will be reduce weight of patient, minimize flawed and reduce depend the other people to activities. This research is observation survey research that the research uses cross section study design are dependent variable and independent variable measure simultaneous. Result of this research shows: (1) Knowledge level family of stroke patient about nursing of patient at home in medium category is 70,8%. (2) Family attitude of Stroke patient in patient nursing at home is 87,5% in medium category. (3) Family behavior of stroke patient in nursing patient at home in good category is 75,0%. (4) There are significant relation between knowledge with attitude in patient stroke with p = 0,049 (5) There are significant relation family and attitude nursing of stroke patient with p = 0,001.